Modeling sloshing damping for spacecraft: A smoothed particle hydrodynamics application - Kotsarinis, K.; Green, M.D.; Simonini, A.; Debarre, O.; Magin, T.; Tafuni, A. (Aerospace science and technology, 2023)
Characterizing the movement of space propellant in the tank subjected to maneuvers and predicting its damping is a fundamental requirement for the success of space missions. In this work, we evaluate the capabilities of the smoothed particle hydrodynamics method (SPH) of characterizing liquid sloshing motion. SPH simulations are performed using the open-source code DualSPHysics, which employs a weakly compressible assumption to simulate incompressible flows. We verify the SPH scheme by showing that the calculated boundary layer matches the analytical solution of the Stokes problem. The methodology is then validated against an open-access experimental database involving sloshing experiments on partially-filled cylindrical tanks subject to horizontal excitations. We present a study of two regimes: (a) a forced, periodic regime and (b) a transient regime where we compare the full liquid interface elevation, the corresponding frequency content and the full liquid interface damping maps. The simulations are able to capture the relevant flow physics with a good level of accuracy. In particular, the simulations fairly accurately reproduced the elevation of the full free surface, predicting a 3D crescent shape of the rising wavefronts, as well as damping rates under free sloshing. Analysis of the frequency range further showed good agreement of the dominant frequencies between the experimental, simulated and analytical values given by the linearized sloshing theory.